Group self-control therapy untuk mengurangi perilaku merokok pada remaja - Ibnu Sutoko; Cahyaning Suryaningrum (Procedia : Studi Kasus dan Intervensi Psikologi, 2022)
Adolescence is a time when individuals are easily inﬂuenced by the environment. One of the environmental exposures during adolescence is the use of cigarettes. Not many teenagers are able to cope with environmental inﬂuences, thus creating a sense of conformity to smoking. The cause of adolescents not being able to overcome conformity is a lack of self-control when in situations that trigger smoking. The purpose of this study is to reduce smoking behavior in adolescents by increasing self-control when in situations that trigger smoking. Subjects consisted of four teenagers aged 16 -18 years old. The assessment method used are interview, observation, Glover-Nilsson Smoking Behavior Questionnaire (GN-SBQ) and self-report. The intervention technique used is group self-control therapy. The results of the intervention showed a gradual decrease in smoking behavior after each group member was able to apply self-control techniques when in situations that trigger smoking. The decrease in smoking behavior can occur because with self-control, each subject in the group can control the sense of conformity that triggers the subject to smoke.